Seed Longevity of Carrot (Daucus carota L.) as Affected by Different Temperatures and Containers during Storage - MANJEET KAUR; GEETA BASSI; RAJINDER SINGH (Seed Research, 2026)
Seeds of carrot (Daucus carota L.) cv. Punjab Carrot Red were stored at three different temperatures (ambient, cold room and refrigerator) in four different packaging materials (cloth bag, plastic bag 700 gauge, desiccator with silica gel and desiccator with drying beads) for 12 months. The longevity and viability of the stored seeds was tested by determining per cent germination, moisture content per cent (MC), vigour index I, vigour index II and speed of germination. Seeds stored at cold room temperature ( 15°C) maintained the Indian Minimum Seed Certification Standards (IMSCS) after 12 months of storage period when packed at MC 5.56±1% and 5.64±1% in desiccator containing desiccants (drying beads and silica gel) respectively. It was at par with that kept in refrigerator ( 5.9°C) when kept in desiccator containing drying beads and silica gel at MC of 5.56±1% and 5.87±1% respectively. Under ambient temperature conditions, cloth bag maintained the IMSCS after 12 month of storage with 6.7±1% of moisture content.